Arterial hypertension and pulse pressure in school-age children - Yu. M. Nechytailo; N. I. Kovtyuk; D. Yu. Nechytailo (Zaporožskij Medicinskij Žurnal)
Childhood arterial hypertension (AH) has become a global problem not only for pediatrics, but also for public health in general.